C-reactive protein: modern state of the problem - V. A. Zhukova; S. A. Shalnova; V. A. Metelskaya (Кардиоваскулярная терапия и профилактика, 2011)
The paper presents the modern views on C-reactive protein (CRP) as a potential risk factor (RF) of atherosclerosis progression. At present, the statement that CRP could be regarded as important as classical RFs (arterial hypertension, dyslipidemia, or smoking) remains controversial. However, CRP is a well-known major inflammatory marker, which is recommended for more accurate risk stratification in clinical practice.